Severe leukopenia in Staphylococcus aureus-necrotizing, community-acquired pneumonia: risk factors and impact on survival - Khanafer, Nagham (BioMed Central, 2013)
BACKGROUND: Necrotizing pneumonia attributed to Panton-Valentine leukocidin-positive Staphylococcus aureus has mainly been reported in otherwise healthy children and young adults, with a high mortality rate. Erythroderma, airway bleeding, and leukopenia have been shown to be predictive of mortality. The objectives of this study were to define the characteristics of patients with severe leukopenia at 48-h hospitalization and to update our data regarding mortality predicting factors in a larger population than we had previously described. METHODS: It was designed as a case-case study nested in a cohort study. A total of 148 cases of community-acquired, necrotizing pneumonia were included. The following data were collected: basic demographic information, medical history, signs and symptoms, radiological findings and laboratory results during the first 48 h of hospitalization. The study population was divided into 2 groups: (1) with severe leukopenia (leukocyte count ≤3,000 leukocytes/mL, n=62) and (2) without severe leukopenia (>3,000 leukocytes/mL, n=86). RESULTS: Median age was 22 years, and the male-to-female gender ratio was 1.5. The overall in-hospital mortality rate was 41.2%. Death occurred in 75.8% of severe leukopenia cases with median survival time of 4 days, and in 16.3% of cases with leukocyte count >3,000/mL (P<0.001). Multivariate analysis indicated that the factors associated with severe leukopenia were influenza-like illness (adjusted odds ratio (aOR) 4.45, 95% CI (95% confidence interval) 1.67-11.88, P=0.003), airway bleeding (aOR 4.53, 95% CI 1.85-11.13, P=0.001) and age over 30 years (aOR 2.69, 95% CI 1.08-6.68, P=0.033). A personal history of furuncles appeared to be protective (OR 0.11, 95% CI 0.01-0.96, P=0.046). CONCLUSION: S. aureus-necrotizing pneumonia is still an extremely severe disease in patients with severe leukopenia. Some factors could distinguish these patients, allowing better initial identification to initiate adapted, rapid administration of appropriate therapy.